The Value Chain of System of Rice Intensification (SRI) Organic Rice of Rural Farms in Kedah - Othman, Siti N; Othman, Zakirah; Yaacob, Noorulsadiqin Azbiya (International Journal of Supply Chain Management, 2016)
System of Rice Intensification ( ability through improving paddy ecosystem, better sustainable economic due to improving paddy production and sales and social sustainability through local community development through community activity and health. This study aimed to find out whether the innovative practices of SRI affect the rice value chain and to determine the roles, activities of the actors in the value chain as well as challenges that impacted the value chain. Using interview as data collection method, case samples were selected from various SRI paddy site in Kedah. The findings indicated that implementing SRI practices in organic paddy cultivation had caused the value chain to be different from conventional paddy value chain in terms of actor and effect of middle man subject to the small scale paddy production. For organic rice value chain to become competitive, roles, activities and challenges were identified so that supports could be provided to the farmers and other related parties in the value chain.